Analisis Sistem Informasi Akuntansi Pengendalian Intern Terhadap Persediaan Bahan Baku PT. Profilindah Kharisma - Khomarudin, Ari Khomarudin (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2018)
Inventory is the main part of working capital which is an asset at any time experiencing changes. In an inventory company has a very important meaning because it will affect the level of production and sales. To ensure that inventory management is in accordance with company management policies, a system is needed that can guarantee the achievement of company objectives. One such system is a system of accounting for raw material inventories. The research design in this study uses qualitative descriptive research. In this study the data collection tool used was by interview. The purpose of this study are: (1) To find out the method of recording raw materials of PT. Profilindah Kharisma, (2) To find out the procedures that make up the raw material inventory system at PT. Profilindah Kharisma, (3) To find out the elements of internal control contained in the accounting system for raw material inventories at PT. Profile of Charisma. The results showed that the accounting system for raw material inventory at PT. Profilindah Kharisma is quite good, this can be seen in the selection of inventory recording method that uses the perpetual method, the method of determining the cost or cost of inventories using the FIFO method, the procedure that establishes a system of accounting for raw material inventories and internal controls contained in the raw material inventory system.